2017
DOI: 10.1186/s12887-016-0774-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-time sickness absence among parents of pre-school children with cerebral palsy, spina bifida and down syndrome: a longitudinal study

Abstract: BackgroundTaking care of a child with special needs can be draining and difficult and require a lot of parental time and resources. The present study investigated the long-term sickness absence of parents who have children with spina bifida, cerebral palsy and Down syndrome compared to that of parents without a child with special needs.MethodsThe sample consisted of primiparae women who gave birth between 2001 and 2005 and the fathers of the children (N = 202,593). Data were obtained from the Medical Birth Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
3
14
0
1
Order By: Relevance
“…1 Further, research has shown that mothers of youth with SB are more likely than fathers to take on the role of managing their child’s medical regimen. 30 Therefore, younger children may be impacted more significantly by maternal SB-specific parenting stress.…”
Section: Discussionmentioning
confidence: 99%
“…1 Further, research has shown that mothers of youth with SB are more likely than fathers to take on the role of managing their child’s medical regimen. 30 Therefore, younger children may be impacted more significantly by maternal SB-specific parenting stress.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fathers of children with more severe conditions perceived their child as being more vulnerable. Research has shown that, in two-parent households, mothers of youth with SB are more likely to take on the role as the child's primary medical caregiver, while fathers are more likely to take on the role of financial providers for the family (Brekke, Fruh, Kvarme, & Holmstrom, 2017). As such, fathers may spend less time and share fewer experiences with their child than do mothers, therefore experiencing fewer positive experiences with their child.…”
Section: Discussionmentioning
confidence: 99%
“…Research has emphasized divergent forms of burden and other predictors of these outcomes including marital quality, economic burden, and psychosocial maladjustment related to high levels of stress (Bannink, van Hove, & Irdro, 2016; Dodgson et al, 2000; Grosse, Flores, Ouyang, Robbins, & Tilford, 2009; Limiñana Gras, Corbalán Berná, & Sánchez López, 2009). Furthermore, it has been found that the burden of care falls particularly on the mother (Brekke, Früh, Kvarme, & Holmstrøm, 2017), and mothers report an increase in depression and anxiety (Civilibal, Suman, Elevli, & Duru, 2014).…”
Section: Impact Of Sb On Familiesmentioning
confidence: 99%